Species Composition, Abundance and Diversity of Lakeshore Birds in Lake Mainit, Agusan del Norte, Philippines - Jr, Eduardo Maca Cabalang (International Journal of Scientific Research in Biological Sciences, 2022)
The aim of this study was to assess the avifaunal diversity of lakeshore birds in the three (3) municipalites of Lake Mainit, Agusan del Norte, Philippines namely Jabonga, Kitcharao and Alegria. It was conducted in fourteen (14) transects for a total of sixty-four (64) hours. Birds were recorded and identified using field guides, visual encounter and bio-acoustic cues. A total of one thousand one hundred twenty eight (1128) individual of birds were documented and resolved into twenty-nine (29) species of lakeshore birds belonging to fourteen (14) families. Ardeidae listed the most number of species seen viz., Purple Heron (Ardea purpurea), Eastern reef-egret (Egretta sacra), Little egret (Egretta garzetta), Javan pond-heron (Ardeola speciosa), Black-crowned night heron (Nycticorax nycticorax), Cattle egret (Bubulcus ibis), Yellow bittern (Ixobrychus sinensis) and Cinnamon bittern (Ixobrychus cinnamomeus). The Common Tern (Sterna hirundo), Javan pond-heron (Ardeola speciosa), Glossy swiftlet (Collocalia esculenta) and Asian glossy starling (Aplonis panayensis), were the most abundant species with a relative abundance of 26.4%, 14.9%, 11.4% and 6.0% respectively. The Cinnamon bittern (Ixobrychus cinnamomeus) and Common Moorhen (Gallinula chloropus) were the least abundant species having 0.08% relative abundance and was encountered once all throughout the survey. Simpson’s index was high at Transect VIII (0.462) and low at transect V (0.089). Based on the IUCN Red List of Threatened Species criteria, one species was considered Vulnerable- the Silvery Kingfisher (Alcedo argentata). This study recommends additional surveys in the areas not covered by this study and a local campaign for the conservation of these lakeshore birds must be implemented to protect and conserve species considered as “vulnerable”.